2023
DOI: 10.1186/s12905-023-02566-y
|View full text |Cite
|
Sign up to set email alerts
|

Does transvaginal natural orifice transluminal endoscopic surgery affect female sexual function?: a prospective cohort study

Abstract: Background To evaluate the effect of transvaginal natural orifice transluminal endoscopic surgery (vNOTES) on female sexual function. Methods: The trial was registered at the Chinese Clinical Trial Registry (ChiCTR2100050887, 07/09/2021). In this prospective cohort study, we prospectively analyzed the data of the female sexual function index (FSFI) questionnaire of 130 patients who underwent laparoscopy in Chengdu Women’s and Children’s Central Hospital due to gynecological benign diseases. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Bucher et al [ 42 ] reported that patients had fears regarding postoperative libido and childbirth outcomes related to vNOTES compared with LESS. Xu et al [ 43 ] assessed and compared the female sexual function index (FSFI) in 130 patients who underwent gynecological surgery (excluding hysterectomy) using vNOTES or transabdominal laparoscopy. There was no statistically significant difference in the total FSFI scores before or at 3 and 6 months postoperatively between the two groups [ 43 ].…”
Section: Vnotes In Benign Gynecologic Conditionsmentioning
confidence: 99%
“…Bucher et al [ 42 ] reported that patients had fears regarding postoperative libido and childbirth outcomes related to vNOTES compared with LESS. Xu et al [ 43 ] assessed and compared the female sexual function index (FSFI) in 130 patients who underwent gynecological surgery (excluding hysterectomy) using vNOTES or transabdominal laparoscopy. There was no statistically significant difference in the total FSFI scores before or at 3 and 6 months postoperatively between the two groups [ 43 ].…”
Section: Vnotes In Benign Gynecologic Conditionsmentioning
confidence: 99%